PEMBELAAN EMANSIPASI PEREMPUAN ISLAM DALAM PUISI “INNAMAL MAR’ATU” KARYA JAMIL SHIDQI AZ-ZAHAWI - Muhammad Jafar Shiddiq (Jurnal Harkat : Media Komunikasi Gender, 2023)
Abstract. This study focuses on analyzing the poem "Innamal Mar'atu" by Jamil Shidqi Az-Zahawi as one of the influential people on the liberation of Muslim women in Iraq in the mid-20th century. The poem will be studied with Paul Ricoheur's Hermeneutic theory supplemented by a literary criticism perspective. feminists to reveal the symbols of defense in the liberation of Islamic women's rights contained therein as a means of criticizing the lives of women who have the impression of sexism towards gender equality which is expected through Paul Ricoheur's heurmenatic stages in the form of semantic, reflective, and philosophical or existential. That the poem contains the defense of Islamic women's rights which Zahawi expressed symbolically in the form of educational and scientific facilities for Muslim women, their role in the family, and social needs so that the life of Islamic society is more egalitarian or equal even though Zahawi's poetry has a history of controversy with the religious dictions conveyed, namely the word "hijab", but with the interpretation of these symbols it makes it read clearly and minimizes misunderstandings in the meaning of Zahawi's poetry. Abstrak. Penelitian ini fokus untuk menganalisis puisi “Innamal Mar’atu” karya Jamil Shidqi Az-Zahawi sebagai salah satu orang yang berpengaruh tentang pembebasan wanita Islam di Irak pada pertengahan abad 20. Puisi tersebut akan dikaji dengan teori Hermeneutik Paul Ricoheur yang dilengkapi dengan perspektif kritik sastra feminis untuk mengungkap simbol-simbol pembelaan dalam pembebasan hak-hak perempuan Islam yang terkandung di dalamnya sebagai sarana kritik terhadap kehidupan perempuan yang terkesan seksisme menuju kesetaraan gender yang diharapkan melalui tahapan-tahapan heurmenatik Paul Ricoheur berupa semantik, reflektif, dan filosofi atau eksistensial. Bahwa di dalam puisi tersebut terkandung pembelaan hak-hak perempuan Islam yang diungkapkan Zahawi secara simbolis berupa fasilitas pendidikan dan keilmuan bagi perempuan Islam, peran mereka dalam keluarga, serta sosial yang dibutuhkan agar kehidupan masyarakat Islam lebih egaliter atau setara meski puisi Zahawi ini memiliki sejarah kontroversi dengan diksi-diksi agama yang dibawakan yaitu kata “hijab”, namun dengan penafsiran simbol-simbol tersebut menjadikannya terbaca dengan jelas dan meminimalisir kesalahpahaman dalam pemaknaan puisi Zahawi ini.